Physiology of alpine skiing - Turnbull, J. R.; Kilding, A. E.; Keogh, J. W. L. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The extreme environment of cold, altitude and movement complexity makes alpine ski racing a difficult sport to study. This review comprises >30 years of research and includes 29 on-snow investigations of specific physiology relating to the various ski racing disciplines, nine off-snow investigations of the physiological capacities of ski racers of varying ability and four review articles. Alpine ski racing appears to involve a complex integration of many different physiological systems, none of which may be more important than the other to overall performance. While technical ability appears to be the greatest influencing factor on performance, the ability to continually exhibit technical competence through a long competitive season requires high capabilities within all physiological systems. Identifying the optimal approach and time to concurrently develop these systems is a challenge for sport scientists. Further research is required using modern portable investigative tools for determining aerobic and anaerobic demands and abilities, especially in the areas of muscle function and relative energy system contribution during both single and multiple runs on varying terrain.